2014
DOI: 10.1016/j.molcel.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Integrator Regulates Transcriptional Initiation and Pause Release following Activation

Abstract: SUMMARY Determining the factors regulating the rate limiting steps in transcriptional control is of fundamental importance to understanding the mechanisms that govern eukaryotic transcription. While studies in unicellular organisms have pointed to initiation as the rate-limiting step in transcription, a large body of work in metazoans indicates that the transition to productive transcriptional elongation may also constitute a critical step. Here, we show that the RNA polymerase II (RNAPII)-associated multi-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
208
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(224 citation statements)
references
References 43 publications
15
208
1
Order By: Relevance
“…Release of the paused polymerase is achieved with P-TEFb phosphorylation of DSIF and NELF, ejecting NELF from pol II and converting DSIF into a positive elongation factor (14,15). The more recent discoveries of additional factors likely involved in pause establishment and release include human capping enzyme (16), the TFIIH-associated kinase, CDK7 (17,18), the TFIIH ERCC3 helicase (19), Mediator (20 -22), Integrator (23,24), ELL (25), TFIIS (26), TRIM28-KAP1-TIF1␤ (27,28), Top1 (29), SEC (30), PAF complex (31,32), and Gdown1 (33). The plethora of factors suggests that more complicated dynamics are at play in regulating pausing and elongation.…”
mentioning
confidence: 99%
“…Release of the paused polymerase is achieved with P-TEFb phosphorylation of DSIF and NELF, ejecting NELF from pol II and converting DSIF into a positive elongation factor (14,15). The more recent discoveries of additional factors likely involved in pause establishment and release include human capping enzyme (16), the TFIIH-associated kinase, CDK7 (17,18), the TFIIH ERCC3 helicase (19), Mediator (20 -22), Integrator (23,24), ELL (25), TFIIS (26), TRIM28-KAP1-TIF1␤ (27,28), Top1 (29), SEC (30), PAF complex (31,32), and Gdown1 (33). The plethora of factors suggests that more complicated dynamics are at play in regulating pausing and elongation.…”
mentioning
confidence: 99%
“…Other than processing the 3 ′ end of snRNAs, Integrator is also implicated in Pol II pause release and transcription elongation (Gardini et al 2014;Yamamoto et al 2014). To distinguish whether the reduced miRNA levels in the absence of Int11 are due to a processing or a transcriptional defect, we carried out RNase protection assays (RPAs) by annealing 32 P-body-labeled RNA probes complementary to pri-miR-HSUR4 with total RNA from transfected 293T cells and digesting with single-strand-specific RNases (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery of Integrator as the long-sought factor in snRNA processing (Baillat et al 2005), new roles have been assigned to the Integrator complex: regulating RNA Pol II transcription promoter-proximal pausing as well as termination (Baillat and Wagner 2015). Chromatin association analyses have shown that Integrator subunits bind to not only snRNA genes but also numerous protein-coding genes (Gardini et al 2014;Stadelmayer et al 2014;Skaar et al 2015). Intriguingly, when Stadelmayer et al (2014) analyzed Integrator-responsive mRNA genes, 40% were found to contain 3 ′ box-like sequences close to the transcription termination site (<1.5 kb).…”
Section: Noncanonical Integrator Substrates On Cellular Rnas?mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that RNA-binding proteins can be associated with specific portions of chromatin, in part because of their interaction with RNA species associated with the transcriptional machinery (34,35). For example, the integrator complex, an snRNA-processing machinery, can be detected at the gene promoters, where it contributes to the regulation of transcriptional initiation and pause release (36). The RNA-binding proteins observed in these chromatin preparations included the RNA helicase DHX40, the RNA-capping enzyme RNMT, the RNA-decapping enzyme DCPS, the RNA cleavage factor CPSF3L, and many others.…”
Section: Significancementioning
confidence: 99%